Evaluation protocol for frenotomy - Gwóźdź-Jezierska, Małgorzata Barbara; Bielecki, Ireneusz (Pediatria Polska - Polish Journal of Paediatrics, 2023)
With the growing interest in the topic of ankyloglossia and the increasing number of frenotomies performed, the need to develop a uniform protocol for clinical management and to define objective indications for the procedure is becoming urgent. This paper presents an interdisciplinary proposal for a procedure for evaluating the indication for frenotomy, developed on the basis of an analysis of existing classifications and a review of the literature from all fields dealing with this topic. The proposed procedure for evaluating the indication for frenotomy is based on an objective and verifiable scoring system, which considers anatomical, functional, and clinical criteria. This approach enables the assessment of postoperative improvement. The suggested approach significantly reduces subjectivity in surgical decision-making. It is a universal method that can be customized to meet individual patient needs. Furthermore, it opens avenues for interdisciplinary and comparative research on ankyloglossia.